Development of an Effective and Efficient Employee Recruitment and Selection System - Sri Rokhani (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The development of an effective and efficient employee recruitment and selection system is an important strategic step to support the success of the organization in achieving its goals. An optimized recruitment and selection process not only aims to get the best candidates, but also ensures proper allocation of resources, both in terms of time and cost. This research focuses on companies engaged in the medical field. After a deeper examination, several problems were found that made the employee recruitment and selection system that had been implemented in the company considered less than optimal in finding new workers. So the purpose of this research is to design a proposal for the development of a more effective and efficient employee recruitment and selection system. The method used in this research is descriptive qualitative research design with data collection through document study, semi-structured interviews with key informants, and field practice during the research. The result of this research is the formation of a proposed design of the company's system development. Starting from the establishment of a Service Level Agreement, Optimizing the company's social media, to the establishment of Standard Operating Procedures for recruitment and selection of new employees. This research concludes that the development of technology-based systems not only improves operational efficiency, but also provides added value in human resource management. Therefore, the implementation of this system is recommended as an innovative solution for organizations that want to compete in the digital era.